Database Evaluation: Policy and Process - Thomas, William Joseph; DuBose, Stefanie (My University, 2006)
Many libraries are facing the challenge of increasing access to electronic resources with static, if not decreasing, materials budgets. Evaluations must be a collaborative mechanism for the acquisition, retention, and cancellation of electronic resources, and they require planning for policy and process before the evaluations themselves may be done. Collaboration and ·ongoing communication are necessary among faculty and staff throughout the library before, during, and after an evaluation. The evaluation process must take into account the current and future curriculum/research needs of the parent institution, how the classes are delivered, and the budget constraints under which libraries operate. On a practical level, the. process must reflect these concerns and include specific criteria regarding content, usability, curriculum needs, and vendors.
Keywords: Academic Libraries